Hepatic Artery Mycotic Aneurysm Associated with Staphylococcal Endocarditis with Successful Treatment: Case Report with Review of the Literature - Dhara Chaudhari; Atif Saleem; Pranav Patel; Sara Khan; Mark Young; Gene LeSage (Case Reports in Hepatology)
Mycotic hepatic artery aneurysm is a vascular pathology associated with bacterial endocarditis. It is rare in occurrence after the introduction of effective antibiotics. We present a young patient with injection drug abuse associated staphylococcal endocarditis which was successfully treated with antibiotics and valve replacement who presented with abdominal pain. He was found to have mycotic aneurysm of hepatic artery which was successfully treated with coil embolization.